Analysis Factors Influencing Intention to Use of Learning Management System - Aditya, Yahya Mulya; Hidayat, Kadarisman; Nuralam, Inggang Perwangsa (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This study examines and analyzes the influence of self-efficacy, facilitating conditions, perceived usefulness, perceived ease of use, and attitude toward using on intention to use LMS. The research method used is a quantitative method with a descriptive approach. Data collection procedures in this study is the respondent's response, which comes from a questionnaire distributed to 154 employees of PT Rantai Pasok Teknologi (FishLog) via Google form and sent via WhatsApp containing opinions or assessments. Structural Equation Modeling Partial Least Square (SEM-PLS) is the analysis tool. The results showed a positive and significant influence on self-efficacy, perceived ease of use, perceived usefulness, attitude toward using, and intention to use. The facilitating conditions factor was found to have an insignificant effect on perceived ease of use. Companies that have used LMS must properly prepare supporting facilities and understand their employees regarding features, benefits, and other things that can keep positive attitudes and employee interest in LMS.Keywords: self-efficacy, facilitating conditions, perceived usefulness, perceived ease of use, attitude toward using, intention to use, extended TAM